Streptococcus thermophilus APC151 Strain Is Suitable for the Manufacture of Naturally GABA-Enriched Bioactive Yogurt - Linares, Daniel M.; O’Callaghan, Tom F.; O’Connor, Paula M.; Ross, R. P.; Stanton, Catherine (Frontiers in Microbiology, 2016)
Consumer interest in health-promoting food products is a major driving force for the increasing global demand of functional (probiotic) dairy foods. Yogurt is considered the ideal medium for delivery of beneficial functional ingredients. Gamma-amino-butyric acid has potential as a bioactive ingredient in functional foods due to its health-promoting properties as an anti-stress, anti-hypertensive, and anti-diabetic agent. Here, we report the use of a novel Streptococcus thermophilus strain, isolated from the digestive tract of fish, for production of yogurt naturally enriched with 2 mg/ml of gamma-amino-butyric acid (200 mg in a standard yogurt volume of 100 ml), a dose in the same range as that provided by some commercially available gamma-amino-butyric acid supplements. The biotechnological suitability of this strain for industrial production of yogurt was demonstrated by comparison with the reference yogurt inoculated with the commercial CH1 starter (Chr. Hansen) widely used in the dairy industry. Both yogurts showed comparable pH curves [ΔpH/Δt = 0.31-0.33 h-1], viscosity [0.49 Pa-s], water holding capacity [72–73%], and chemical composition [moisture (87–88%), protein (5.05–5.65%), fat (0.12–0.15%), sugar (4.8–5.8%), and ash (0.74–1.2%)]. Gamma-amino-butyric acid was not detected in the control yogurt. In conclusion, the S. thermophilus APC151 strain reported here provides a natural means for fortification of yogurt with gamma-amino-butyric acid.